Degree of acceptance of a learning assessment model based on competencies - Díaz Pinedo, Moisés (2013)
In this article we consider the importance of evaluation models based on competencies. First, we find the background that led to its realization, as a preamble to the problem is solved. It also considers the degree of acceptance of competencybased model. Then, we present the methodological processes that were used to provide an empirical answer and its agreement with the theory. Among the findings it was found that the learning assessment model sample acceptance levels (75.25%). It also is recommended to set an evaluation system under a model such as this, which integrates performance, performance, scope, goals and achievement clear and well defined, that is also reliable and allow the identification of the level of efficiency are performed individual and group activities.